Intramolecularly‐stabilized Group 14 Alkoxides – Promising Precursors for the Synthesis of Group 14‐Chalcogenides by Hot‐Injection Method. Issue 11 (11th April 2017) - Rusek, Monika; Bendt, Georg; Wölper, Christoph; Bläser, Dieter; Schulz, Stephan
Abstract : Intramolecularly‐stabilized germanium, tin, and lead alkoxides of the type M (OCH2 CH2 N R 2 )2 [ R = Et, M = Ge (1 ); R = Me, M = Sn (2 ); R = Me, M = Pb (3 )] are suitable precursors for the synthesis of group 14 chalcogenides ME ( M = Ge, Sn, Pb; E = S, Se, Te) in scrambling reactions with (Me3 Si)2 S and (Et3 Si)2 E ( E = Se, Te) at moderate temperatures via hot injection method. The reactions proceed with elimination of the corresponding silylether as was proven by in situ 1 H NMR spectroscopy. The solid‐state structures of the homoleptic complex1 and the heteroleptic complex ClGe(OC2 H4 NEt2 ) (4 ) were determined by single‐crystal X‐ray diffraction, whereas the group 14 chalcogenides were characterized by XRD, SEM, and EDX. Abstract :